PENERAPAN MULTIMEDIA INTERAKTIF BERBASIS POWERPOINT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V DI SDN BANJARMADU - Afandi, Yusuf; MZ, A.F. Suryaning Ati; Zativalen, Oriza (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to improve the learning outcomes of fifth-grade students at SDN Banjarmadu through the implementation of interactive PowerPoint-based learning media. The research employed a Classroom Action Research (CAR) method consisting of two cycles, each including planning, implementation, observation, and reflection stages. The participants were 24 fifth-grade students. The instruments used included observation sheets for teacher and student activities, as well as learning outcome tests. The results showed that the implementation of interactive PowerPoint media improved both teacher and student activities, as well as students’ learning outcomes. This was evidenced by the increase in observation scores and test results from Cycle I to Cycle II. Students’ learning outcomes improved from 66.7% in Cycle I to 79.2% in Cycle II, indicating an increase of 12.5%. In conclusion, interactive PowerPoint media is effective in enhancing students’ learning outcomes in Integrated Science and Social Studies (IPAS) at the elementary school level.